PERBANDINGAN MODEL PEMBELAJARAN VIA BERTELEPON DAN TUTOR TEMAN SEBAYA DENGAN MODEL PEMBELAJARAN TIPE MinDS DAN TIPE MAKING A CONVERSATION UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI - Yayu Laila Sulastri; Didin Wahidin; Deti Ahmatika (UJMES (Uninus Journal of Mathematics Education and Science), 2017)
The problem in this research is the lack of readiness of the practitioner students to practice in the field and the low ability ofhigh-order thinking of the students of praktikan. The purpose of this research is to know the comparison by using four activelearning models to improve students' high thinking ability. This research uses Research and Development method, with firstphase design, preliminary study done by applying qualitative descriptive approach. The second stage, the development of modeldesign, teaching materials web-based learning media by applying a descriptive approach, followed by the application of smallscopes of model design, teaching materials, and web-based learning media by applying the experimental method (Single OneShot Case Study). The results of the limited trials show that the average value of higher-order thinking skills for the guideddiscovery-based learning model and peer instruction is higher than the MinDS and Making A Conversation type of learningmodel. The findings of the limited trial result of the four guided discovery learning models are more suitable for improvingthe activity as well as the material content of the design of discovery learning activities (KBP) still confuses the students, sothere needs to be improvement.